Development of a simple, rapid sandwich enzyme immunoassay for the measurement of serum rat LH (Revista Española de Fisiología, 1996)
The present study describes the development and validation of a rapid, sensitive, specific and precise enzyme immunoassay (EIA) sandwich suitable for measuring luteinizing hormone (LH) in rat serum. Ninety-six well polystyrene microtiter plates were coated with 100 pl (250 ng/ml) of a well-characterized monoclonal antibody (518B7, Roser, UC Davis) generated against bovine LH. A polyclonal antiserum raised in rabbits against ovine FSH (G4-215B, Papkoff) was conjugated to sodium periodate-activated horseradish peroxidase (HRP), and used as the second antibody of the sandwich assay. This anti-ovine FSH antiserum cross-reacted more than 200 % with rat LH. Standards (r-LH-RP-3, NIADDK, range 0 pg/well to 2.5 ng/well or 100 p.1) diluted in a 3(N-Morpholino) propane sulfonic acid (MOPS) buffer, or serum, were incubated with the solid phase antibody for 2 hours. Plates were washed and the anti-oFSH:HRP (100 pl) in MOPS buffer was added and incubated a further 2 hours before a second wash and the addition of the substrate (TMB, 3,3’,5,5’-tetramethylbenzidine dihydrochloride and H2O2). The least detectable concentration of LH was 16.1 ± 1.42 pg/ml. The recovery of known concentrations of LH added to several samples was 93.5 ± 1.70 %. Mean intra-assay and inter-assay coefficients of variation (%) were less than 10 % (n = 20). The anti-FSH:HRP showed less than 8.0 % cross reactivity with rFSH in this LH EIA system. The correlation coefficient (r) of samples analyzed by EIA in parallel with RIA was r = 0.90 (p < 0.001, n = 26). Results showed levels between 105.21 and 633.87 pg/ml. This new LH EIA sandwich offers a stable, rapid, and improved EIA system for the measurement of serum LH concentrations of this species over previously reported methods.The present study describes the development and validation of a rapid, sensitive, specific and precise enzyme immunoassay (EIA) sandwich suitable for measuring luteinizing hormone (LH) in rat serum. Ninety-six well polystyrene microtiter plates were coated with 100 pl (250 ng/ml) of a well-characterized monoclonal antibody (518B7, Roser, UC Davis) generated against bovine LH. A polyclonal antiserum raised in rabbits against ovine FSH (G4-215B, Papkoff) was conjugated to sodium periodate-activated horseradish peroxidase (HRP), and used as the second antibody of the sandwich assay. This anti-ovine FSH antiserum cross-reacted more than 200 % with rat LH. Standards (r-LH-RP-3, NIADDK, range 0 pg/well to 2.5 ng/well or 100 p.1) diluted in a 3(N-Morpholino) propane sulfonic acid (MOPS) buffer, or serum, were incubated with the solid phase antibody for 2 hours. Plates were washed and the anti-oFSH:HRP (100 pl) in MOPS buffer was added and incubated a further 2 hours before a second wash and the addition of the substrate (TMB, 3,3’,5,5’-tetramethylbenzidine dihydrochloride and H2O2). The least detectable concentration of LH was 16.1 ± 1.42 pg/ml. The recovery of known concentrations of LH added to several samples was 93.5 ± 1.70 %. Mean intra-assay and inter-assay coefficients of variation (%) were less than 10 % (n = 20). The anti-FSH:HRP showed less than 8.0 % cross reactivity with rFSH in this LH EIA system. The correlation coefficient (r) of samples analyzed by EIA in parallel with RIA was r = 0.90 (p < 0.001, n = 26). Results showed levels between 105.21 and 633.87 pg/ml. This new LH EIA sandwich offers a stable, rapid, and improved EIA system for the measurement of serum LH concentrations of this species over previously reported methods.